2021
DOI: 10.1073/pnas.2102225118
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the “fungal shunt”: Parasitic fungi on diatoms affect carbon flow and bacterial communities in aquatic microbial food webs

Abstract: Microbial interactions in aquatic environments profoundly affect global biogeochemical cycles, but the role of microparasites has been largely overlooked. Using a model pathosystem, we studied hitherto cryptic interactions between microparasitic fungi (chytrid Rhizophydiales), their diatom host Asterionella, and cell-associated and free-living bacteria. We analyzed the effect of fungal infections on microbial abundances, bacterial taxonomy, cell-to-cell carbon transfer, and cell-specific nitrate-based growth u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 102 publications
3
59
0
Order By: Relevance
“…Chytridiomycetes are known to parasitize algae, directly deriving OM from them rather than through decomposition, and potentially fostering the release of macromolecules through cell death and disruption of the cell walls (Senga et al, 2018). The relevance of these parasitic fungi for the production of a “fungal shunt” and related carbon fluxes is increasingly being recognized in aquatic ecosystems (Klawonn et al, 2021), including cryospheric ecosystems (Anesio et al, 2017; Brown et al, 2015). The apparent dominance of these parasitic fungi suggests that the majority of GFS fungi are primarily using algae‐derived OM (e.g., from Hydrurus ) rather than allochthonous OM from glacier ice or terrestrial vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…Chytridiomycetes are known to parasitize algae, directly deriving OM from them rather than through decomposition, and potentially fostering the release of macromolecules through cell death and disruption of the cell walls (Senga et al, 2018). The relevance of these parasitic fungi for the production of a “fungal shunt” and related carbon fluxes is increasingly being recognized in aquatic ecosystems (Klawonn et al, 2021), including cryospheric ecosystems (Anesio et al, 2017; Brown et al, 2015). The apparent dominance of these parasitic fungi suggests that the majority of GFS fungi are primarily using algae‐derived OM (e.g., from Hydrurus ) rather than allochthonous OM from glacier ice or terrestrial vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on recent studies, marine fungal communities are dominated by members of the phylum Ascomycota (Tisthammer et al, 2016;Amend et al, 2019;Hassett et al, 2019a) and Chytridiomycota (Comeau et al, 2016;Hassett and Gradinger, 2016;Hassett et al, 2017;Richards et al, 2021). Chytridiomycota, frequently referred to as chytrids, are often recognized as zoosporic virulent parasites on phytoplankton which play significant roles in controlling population sizes of their hosts (Ibelings et al, 2004;Kagami et al, 2004;Rasconi et al, 2011) and altering food web structure by transferring carbon and energy between trophic levels (Rasconi et al, 2012(Rasconi et al, , 2020Sime-Ngando and Twiss, 2012;Klawonn et al, 2021b). The majority of quantitative studies of zoosporic fungi to date have been laboratory-based, with only a small number of field studies conducted to assess their importance into the broader environment.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, one estimate reported that 50–70% of host biomass is made available for bacterial remineralization during Syndiniales infections of the dinoflagellate Akashiwo sanguinea (Yih and Coats 2000). Parasitic chytrid fungi, also newly recognized as abundant members of ocean microbial communities, may decrease phytoplankton DOC release by directing carbon into fungal biomass (Klawonn et al 2021). Quantification of marine protist and fungal parasite contributions to the labile DOC pool awaits a better understanding of their basic ecological dynamics (e.g., infection patterns, host preferences; Anderson and Harvey 2020) and field methodology to tease apart parasite‐released DOC from that of other sources.…”
Section: The Sourcesmentioning
confidence: 99%